The Effect of Praise of Worship and Preaching of God's Word on The Spiritual Improvement of The Congregation at The Indonesian Bethel Church Victorious Family Kelapa Gading - Chendralisan, Lenny Helena Sacharissa (LP. Ma'arif Janggan Magetan, 2024)
This research examines the impact of praise and worship and the preaching of God’s Word on congregational spiritual growth at Gereja Bethel Indonesia Victorious Family Kelapa Gading. Spiritual growth is a core objective of church ministry, shaped by various internal factors. Among these, praise and worship, along with preaching, are key instruments fostering faith maturity and individual spiritual development. Using a quantitative approach, data were collected via questionnaires from congregants and church workers. The findings reveal a positive and significant combined influence of praise and worship and preaching on congregational spiritual growth. Regression analysis indicates a correlation coefficient (R) of 0.759, meaning these elements account for 75.9% of the influence, while the remainder is shaped by other factors. The results highlight the need for the church to continuously enhance the quality of praise, worship, and preaching in services and programs, while encouraging active participation and personal spiritual discipline among members. This study contributes to practical theology and offers guidance for church ministry strategies aimed at fostering a spiritually mature congregation. Overall, the research emphasizes that intentional and well-integrated worship practices significantly support the spiritual formation of church members, making them essential components in the pursuit of holistic congregational growth.